2006
DOI: 10.1093/annonc/mdj094
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of randomised, controlled trials of the timing of chest radiotherapy in patients with limited-stage, small-cell lung cancer

Abstract: There are indications that the 5-year survival rates of patients with LS-SCLC are in favour of early chest radiotherapy, with a significant difference if the overall treatment time of chest radiation is less than 30 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
82
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 31 publications
2
82
1
2
Order By: Relevance
“…That finding is again supported by the Murray et al trial 19 , despite a similar rct conducted in the United Kingdom, which suggested no os benefit for early compared with late ccrt 23 . A meta-analysis by De Ruysscher et al 24 of trials evaluating the timing of ccrt showed a trend toward improved os with early ccrt, particularly if the chemotherapy was platinum-based. The convert trial also mandated early ccrt, and because many Canadian centres were involved in that trial, their involvement likely influenced our findings.…”
Section: Discussionmentioning
confidence: 99%
“…That finding is again supported by the Murray et al trial 19 , despite a similar rct conducted in the United Kingdom, which suggested no os benefit for early compared with late ccrt 23 . A meta-analysis by De Ruysscher et al 24 of trials evaluating the timing of ccrt showed a trend toward improved os with early ccrt, particularly if the chemotherapy was platinum-based. The convert trial also mandated early ccrt, and because many Canadian centres were involved in that trial, their involvement likely influenced our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline characteristics were similar between the early and late PCI groups; therefore, this result was not confounded by other clinical factors. It is well established that early chest radiotherapy may improve the survival rate of patients with LS-SCLC (22). As a prophylactic treatment, it is unknown whether early PCI may be as effective as early chest radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of TRT concurrent with chemotherapy, during the first two cycles, and a start to end of radiotherapy Ͻ30 days appear to improve the efficacy of chemoradiotherapy. The data from individual trials investigating the timing of TRT are contradictory, but three meta-analyses [20,21,32], based on published data, suggest that TRT should be started early, and an accelerated regimen should be considered in combination with platinum-based therapy. A meta-analysis based on individual data may provide additional information about the optimal time to initiation of TRT and a better estimate of the magnitude of benefit.…”
Section: Discussionmentioning
confidence: 99%